2017
DOI: 10.3390/w9070516
|View full text |Cite
|
Sign up to set email alerts
|

End-User Cost-Benefit Prioritization for Selecting Rainwater Harvesting and Greywater Reuse in Social Housing

Abstract: Rainwater harvesting (RWH) and greywater reuse (GWR) are increasingly being considered at the building-level to achieve multiple goals. Cost-benefit assessments facilitate decision-making; however, most are focused on large-scale systems with limited information available for households from developing countries. To better understand the prioritization of costs and benefits by potential end-users in this context, this paper presents an assessment of an RWH/GWR system in low income, low consumption households i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…It makes up the largest proportion of the total wastewater flow from homes (water discharged from washing machines, showers, tubs, and bathroom sinks), and it has a very low nutrient content; moreover, it is generated regardless of climate conditions. In terms of daily production, the scientific literature indicates that the greywater volumes can represent from the 50% to the 80% of the total in-house water demand (Domínguez et al, 2017), those values are similar to those found in Italy, during the monitoring activities carried out within the AQUASAVE project (LIFE 97 ENV/IT/000106). This project showed that the average water consumption of potable water in a residential building, equipped with low consumption devices, is about 106.35 l/p/d of which 23% is used for toilet flushing; 12% for dishwashers and washing machines, 4% for food preparation, and 28% for other uses (Failla et al, 2001).…”
supporting
confidence: 64%
See 1 more Smart Citation
“…It makes up the largest proportion of the total wastewater flow from homes (water discharged from washing machines, showers, tubs, and bathroom sinks), and it has a very low nutrient content; moreover, it is generated regardless of climate conditions. In terms of daily production, the scientific literature indicates that the greywater volumes can represent from the 50% to the 80% of the total in-house water demand (Domínguez et al, 2017), those values are similar to those found in Italy, during the monitoring activities carried out within the AQUASAVE project (LIFE 97 ENV/IT/000106). This project showed that the average water consumption of potable water in a residential building, equipped with low consumption devices, is about 106.35 l/p/d of which 23% is used for toilet flushing; 12% for dishwashers and washing machines, 4% for food preparation, and 28% for other uses (Failla et al, 2001).…”
supporting
confidence: 64%
“…The amount of water harvested varies depending on rainfall intensity, household size, roof size and type, and average dry weather period between rainfall events. Consequently, the water saving efficiency can range from less than 1% up to 100% (Domínguez et al, 2017;Ghisi and Mengotti de Oliveira, 2007).…”
mentioning
confidence: 99%
“…In order to promote potable water savings in buildings, several studies about water-saving plumbing fixtures, greywater reuse, and rainwater harvesting have been carried out [2,[4][5][6][7][8][9][10][11][12]. In these studies, the authors determined potable water savings in buildings due to the adoption of one or more of these strategies.…”
Section: Introductionmentioning
confidence: 99%
“…In residential buildings, wastewater is produced by bathroom sinks, showers, and bathtubs, while kitchen water is excluded due to the high levels of organic matter and solids along with foodborne pathogens [5,6]. Despite in some countries the end-user acceptability for greywater systems is still limited by hygiene concerns [7], this technology has a considerable advantage: greywater is a year-round continuous source of water for non-potable use, reducing demand from local water supplies and impacts from discharge.…”
Section: Introductionmentioning
confidence: 99%